SHARIA COMPLIANCE IN ISLAMIC BANKING IN INDONESIA: LEGAL CHALLENGES AND OPPORTUNITIES IN THE DIGITAL AGE - Nasution, Emmi Rahmiwita (Kanun Jurnal Ilmu Hukum, 2025)
Although the adoption of technologies such as blockchain, artificial intelligence, and mobile banking is progressing rapidly, significant challenges remain in ensuring that these innovations comply with Sharia principles while building customer trust. This study is driven by regulatory gaps in accommodating digital transactions, particularly electronic contracts, data protection, and cross-border services within the framework of Sharia compliance. This study examine the legal challenges and opportunities arising from digital transformation in Islamic banking, focusing on the extent to which existing laws, including Law No. 21/2008, DSN MUI fatwas, and OJK regulations, can support innovation. Using a normative juridical approach through literature review and legal analysis, this study hypothesizes that strengthening regulatory clarity and encouraging collaboration between regulators, financial institutions, and technology providers is crucial to maintaining Sharia-compliant digital finance. The findings show that although digital technology improves efficiency and inclusion, its effectiveness depends on the development of flexible regulations and customer trust in Sharia-compliant digital products. This provides practical recommendations for policymakers and Islamic financial institutions to balance innovation with Sharia compliance, thereby positioning Indonesia as a potential leader in global Islamic digital finance.